Single-Species Co-management Improves Fish Assemblage Structure and Composition in a Tropical River - Medeiros-Leal, Wendell M.; Castello, Leandro; Freitas, Carlos E. C.; Siqueira-Souza, Flávia K. (Frontiers in Ecology and Evolution, 2021)
Co-management is increasingly recognized as an effective model for managing fisheries, but little information exists on whether co-management can produce effects in species other than the target species. Fishery co-management in the tropics, where fish diversity is high and fish catches tend to be multispecies, is prone to produce assemblage-wide effects via alterations in the food web and changes in the overall capture of non-target species. Here, we assessed the effects of co-management for the species Arapaima sp. in relation to the structure and composition of the overall fish assemblage in floodplain lakes of the central Amazon Basin. These floodplain lakes are managed under a system of zoning of fishing activities. We used data from surveys of six floodplain lakes, including two lakes of each of three categories (lakes where fishing is prohibited, limited-access lakes and open fishing lakes). The surveys were carried out before and after implementation of co-management, through gillnet fishing. The study area was the lower Solimões River, in the Amazon Basin, Brazil. Statistical models showed significant changes in the composition and structure of the fish assemblages after the implementation of the co-management, regardless of the zoning category. Through regulation of gear use and fishing practices, co-management allowed the colonization of species that had not been present before, which lead to higher richness and consequently increased fish sizes, abundance and biomass. Species of sedentary habits, migrants of short and medium distances, with commercial importance benefitted the most from co-management. In the results presented in temporal scale, it was possible to observe a potential spillover effect being provided by the lakes where fishing is prohibited (no-take zones) and those of limited access that benefitted those open to fishing. Thus, co-management had positive effects in the structure and composition of fish assemblages in all lakes, regardless of zoning category.